Modality in Climate Change-Related Discourse by King Charles III - Oleksandr Kapranov (ES Review)
The article presents a corpus-based study that aims at establishing how modality is used in climate change-related discourse by King Charles III of the United Kingdom of Great Britain and Northern Ireland (the UK). The study involved a corpus of speeches on the topic of climate change delivered by King Charles III from 2005 to 2023. The corpus was analysed in the computer software AntConc (Anthony) in order to compute the frequency of the occurrence of the central modal verbs. Thereafter, they were analysed qualitatively to establish the types of modality associated with them. The analysis revealed that climate change-related discourse by King Charles III was marked by a high frequency of the occurrence of the modal verbs will and can. Their frequency, pragmatic roles, and association with the different types of modality are further discussed in the article.